Geomorphological map of the Northern Foothills near the Italian Station, (Terra Nova Bay, Antarctica). - BARONI, CARLO (1987)
A detailed colour geomorphological map is here presented. The map has been drawn at the scale of 1:20.000 and is intended to be a base for future geomorphological and environmental studies. The geomorphological mapping has been conducted according to the manual of DEMEK and more recent geomorphological maps produced in Italy by the National Group of Physical Geography and Geomorphology of the CNR. Landforms and deposits mapped include those related to glaciers, cryogenic activity, wind and sea action, weathering and geological structure. They have been represented with distinct colours referred to the geomorphic processes which they originated from. Lithologic and structural features are also supplied. A pattern conditioned by the geological structure and by the glacial history can be outlined. Several zones parallel to the coast can be singled out. A first, lower belt is characterized by coastal landforms, strongly conditioned by salt weathering and showing organogenous features. Due to the isostatic rebound, the marine influence during the Holocene has interested directly a belt ranging in altitude from the present sea level up to about 30 m a.s.l. A wider coastal zone is indirectly conditioned by the sea through salt weathering, strongly efficient on the coarse granitic rocks, that are widely affected by alveols and deep tafoni. A second belt can be recognized up to about 350 m, corresponding to the area covered by the ice during the last glaciation. A discontinuous sheet of glacial sediment is present; it is locally ice-cored and widely affected by ice-wedge polygons. Large areas of debris covered glaciers are also present. A third belt develops higher than 350 m, up to the maximum height present in the surveyed area. Large bedrock outcrops with a thin and highly discontinuous cover of glacial sediments occur in this belt. Rock surfaces are strongly oxidized, show frequent cavernous weathering, and locally, pseudo-karren features. The local glaciers and snowfields grow on the lee-side of the hills and are ...